PENGARUH KUALITAS PELAYANAN PUBLIK TERHADAP KEPUASAN MASYARAKAT DI KANTOR KECAMATAN JAYANTI - Mila Alfionita; Iba Gunawan (FKIP, Universitas Banten Jaya, 2020)
This study aims to determine the effect of service quality on community satisfaction in the Jayanti District office. Samples taken by researchers are 100 respondents from a total population of 60,091 inhabitants. For data collection in this study using a questionnaire.The analysis technique used to see the effect of service quality on community satisfaction in the Jayanti District office is a quantitative method that uses SPSS calculations.The results showed that there was a close relationship between service quality and community satisfaction as seen from the results of the coefficient obtained at 72.7%. Partially shows that the significant value for the effect of service quality on community satisfaction is 0.042 <0.05 and tcount 2.648> t table 1.665, so Ho is rejected and Ha is accepted. This means that there is an influence between service quality and community satisfaction.